2018
DOI: 10.1016/j.ymthe.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

4Mu Decreases CD47 Expression on Hepatic Cancer Stem Cells and Primes a Potent Antitumor T Cell Response Induced by Interleukin-12

Abstract: The tumor microenvironment (TME) represents a complex interplay between different cellular components, including tumor cells and cancer stem cells (CSCs), with the associated stroma; such interaction promotes tumor immune escape and sustains tumor growth. Several experimental approaches for cancer therapy are focused on TME remodeling, resulting in increased antitumor effects. We previously demonstrated that the hyaluronan synthesis inhibitor 4-methylumbelliferone (4Mu) decreases liver fibrosis and induces ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 65 publications
0
39
0
Order By: Relevance
“…HCSCs are hierarchical cell populations of HCC, which are able to initiate and maintain tumor growth, and they have the dual properties of normal stem cells and tumor cells (Sukowati, 2019). As far as we know, CD90, EpCAM, CD133, CD24, CD13, CD34, SOX9, ABCG2, CD44, ALDH, CK19, SOX12, and CD47 are widely recognized as HCSC markers (Ma et al, 2008;Yang et al, 2008;Yamashita et al, 2009;Haraguchi et al, 2010;Lee et al, 2011;Zhang et al, 2013;Fernando et al, 2015;Kawai et al, 2015;Park et al, 2015;Li W. et al, 2017;Richtig et al, 2017;Zou et al, 2017;Rodríguez et al, 2018;Wang et al, 2019), whose combination may result in a wide variety of HCSC phenotypes. Up to date, the majority of HCSC studies focus on identification of the markers for the enriched cell populations that have high tumor initiation ability in immune-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCSCs are hierarchical cell populations of HCC, which are able to initiate and maintain tumor growth, and they have the dual properties of normal stem cells and tumor cells (Sukowati, 2019). As far as we know, CD90, EpCAM, CD133, CD24, CD13, CD34, SOX9, ABCG2, CD44, ALDH, CK19, SOX12, and CD47 are widely recognized as HCSC markers (Ma et al, 2008;Yang et al, 2008;Yamashita et al, 2009;Haraguchi et al, 2010;Lee et al, 2011;Zhang et al, 2013;Fernando et al, 2015;Kawai et al, 2015;Park et al, 2015;Li W. et al, 2017;Richtig et al, 2017;Zou et al, 2017;Rodríguez et al, 2018;Wang et al, 2019), whose combination may result in a wide variety of HCSC phenotypes. Up to date, the majority of HCSC studies focus on identification of the markers for the enriched cell populations that have high tumor initiation ability in immune-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…CD133 (PROM1) was first proposed to be a specific HCSC marker in 2006 (Suetsugi et al, 2006). After that, others were identified, including CD90 (THY1), epithelial cell adhesion molecules (EpCAM), CD24, CD13 (ANPEP), CD34, sex determining region Y-box 9 (SOX9), ATP-binding cassette, subfamily G, member 2 (ABCG2), CD44, aldehyde dehydrogenase (ALDH), CK19 (KRT19), sex determining region Y-box 12 (SOX12), and CD47 (Ma et al, 2008;Yang et al, 2008;Yamashita et al, 2009;Haraguchi et al, 2010;Lee et al, 2011;Zhang et al, 2013;Fernando et al, 2015;Kawai et al, 2015;Park et al, 2015;Li W. et al, 2017;Richtig et al, 2017;Zou et al, 2017;Rodríguez et al, 2018;Wang et al, 2019). Various HCSC markers correlate with diversified forms of cells.…”
Section: Introductionmentioning
confidence: 99%
“…22 In 2018, 4-methylumbelliferone (4Mu) can downregulate the expression of CD47 (marker of tumor cells and cancer stem cells) in hepatocellular carcinoma, resulting in enhanced phagocytosis of antigenpresenting cells and elicited potent cytotoxic-specific T cell response. 23 Recent studies on mice have shown that the blockade of CD47-SIRPα interaction not only enhances the phagocytic activity of phagocytes against tumor cells but also promotes the stimulation of tumorspecific cytotoxic T cells by macrophages or dendritic cells 24 (Figure 1). Many animal experiments on CD47 immunotherapy of tumors have emerged, and researchers believe that CD47 immunotherapy could be a novel strategy for tumor treatment and metastasis prevention.…”
Section: Evolutionmentioning
confidence: 99%
“…This antitumor property could be associated with an inhibition of angiogenesis and decrease in IL-6 production (19). Furthermore, animal survival was increased when CD133 low HCC cells, generated upon 4-MU treatment, were injected in a metastatic HCC model (105).…”
Section: Targeting the Microenvironment To Inhibit Tumor Growthmentioning
confidence: 99%